(untitled) (Research, Society and Development, 2020)
Raw milk is a food with great consumption and economic value in Brazil. However, is susceptible of contamination by pathogenic bacteria. The aimed of this study was to evaluate the quality of in natura milk based on microbiological in three dairy farms, somatic cells counting (SCC), bacterial counting and his physical-chemical composition. Were made the following microbiological analysis: counting of mesophilic and psychrotrophic bacteria, coliforms at 30 ºC, coliforms at 45 ºC, Staphylococcus spp., Listeria spp., and SCC. The physical-chemical analysis was fat, protein, lactose, total solids, urea, and casein. There was no evidence of Salmonella spp. and Escherichia coli were identified in any samples. In accordance to the microbiological standards established by Normative Instruction 76 only coliforms 30 ºC and 45 ºC counts were above the standards. There was a significant difference (p≤0.05) between the three farms studied regarding most microbiological aspects. Also, was observed difference (p≤0.05) for most of physical-chemical aspects. Overall, the milk produced in the regions of Alagoas State fails to meet just a constant criterion in the current legislation.